P01.18.B Structural abnormalities related to chemotherapy in cancer survivors: an ALE meta-analysis of neuroimaging studies. (5th September 2022) - Ahmed, Y; Al-Bzour, A; Al-Majali, G; Ababneh, O; Ibrahim, R; Al-Khalili, A; Hamza, A; Alzghoul, S; Al-Mannai, R; Z Alawneh, K; Al-Hayek, K; Al Qawasmeh, M
Abstract: Background: Chemotherapy induced cognitive impairment (CICI) is a term used for the cognitive dysfunction reported with non-central nervous system cancer patients during or after chemotherapy. Recent neuroimaging studies have shown decreased activation in cancer patients during cognitive tasks post-chemotherapy. Structural changes are sought to be associated with cognitive decline in cancer survivors after chemotherapy. Here we aim to investigate the neuroimaging findings of structural abnormalities and gray matter alterations associated with chemotherapy in cancer survivors. Material and Methods: A systematic search through PubMed database for peer-reviewed English-language studies yielded a total of 302 studies. Eligible studies were included in the activation likelihood estimation (ALE) meta-analysis if they reported coordinates in a stereotactic format (MNI or Talairach space) for voxel-based morphometric (VBM) studies on gray matter volume and post-chemotherapy cancer survivors compared to matched healthy controls. GingerALE (3.0.2) software from Brainmap.org was used to perform the ALE meta-analysis with threshold settings of uncorrected P-value < 0.001 for multiple comparisons. Results: The study sample included 299 patients comprised of breast cancer survivors (BCS), childhood acute lymphocytic leukemia (ALL) survivors, ovarian cancer survivors (OCS) and lung cancer with 279 matched healthy controls from 12 studies and 21 experiments. ALE-maps for post-chemotherapy cancer survivors showed reduced gray matter volume in comparison to healthy controls in the left inferior frontal gyrus, right thalamus, right superior frontal gyrus, right medial frontal gyrus and right cerebellum (peak coordinates: [-43, 40, -6], [23, -29, 2], [14, 30, 55], [9, 57, -16], [9, -78, -41] respectively, and cluster size of 544 mm3, 312 mm3 and 257 mm3, 296 mm3, 297 mm3 respectively). Conclusion: This is the first ALE meta-analysis that studied the converged areas of reduced gray matter volume in post-chemotherapy cancer survivors. Our findings of reduced gray matter volume in frontal regions and cerebellum might be responsible for the cognitive dysfunction in executive function, attention, and memory observed in cancer survivors. Further studies are needed to assess the impact of different chemotherapeutic regimens related to CICI .